General Aviation Pilots Over 70 Years Old - Vuorio, Alpo; Asmayawati, Saryani; Budowle, Bruce; Griffiths, Robin; Strandberg, Timo; Kuoppala, Jaana; Sajantila, Antti (Aerospace Medical Association, 2017)
BACKGROUND: Currently it is not unusual for general aviation pilots in the United States to continue to fly beyond the age of 70, even into their 80s and 90s. Pilots have regular examinations according to protocols which do not specify special or additional requirements for pilots over 70 yr of age. Additionally, the third class medical reforms passed by the U.S. Senate on 15 July 2016 could potentially result in even less stringent medical certification requirements for general aviation pilots. METHODS: Accident rates, medical parameters, autopsy findings, and toxicological findings from the U.S. National Transportation Safety Board (NTSB) general aviation (GA) accident database were analyzed to assess potential risk factors with accident outcomes. RESULTS: During 2003–2012, there were 114 (113 men, 1 woman) general aviation fatal accidents involving pilots ages 70 to 92 yr. A combination of 3 or more drugs were found in 13 (13%) of deceased pilots. The most frequent drugs were first generation antihistamines and antidepressants represented the next highest proportion of possible performance-affecting medications. CONCLUSION: This study indicates that there are critical medical factors that may contribute to fatal accidents among elderly pilots. Polypharmacy use should be taken into consideration, especially during periodic health examinations and fatal aviation investigations involving elderly pilots.
Keywords: accident; antidepressants; drugs; fatal; polypharmacy